2019
DOI: 10.15388/10.15388/ioi.2019.01
|View full text |Cite
|
Sign up to set email alerts
|

TLCS: A Digital Library with Resources to Teach and Learn Computer Science

Abstract: Nowadays, teaching and learning computer science is done at various ages, for several topics and for different reasons. Depending on the country, it can start from the primary school and it finishes at the higher education level, or even later if we take continuing education into consideration. Topics to be learned can be as simple as binary representation or basic programming concepts that can be taught to children to introduce them to computer science. It is also possible to teach and learn advanced data str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Yao, B. demonstrated the importance of the teaching skills resource base for the teacher's teaching ability training and put forward to speed up the teaching skills development resource base of the informatization construction and optimization and continue to promote the progress of teachers' teaching level [16]. Combefis S et al built a teaching resource database platform for mathematics and computer-assisted learning, which supports students to carry out free searches for rich teaching resources and, to a certain extent, promotes the enhancement of students' independent learning ability and the progress of their learning performance [17]. Lan, Y. researched and built a Lan, Y. researched and constructed knowledge system of database design course with computational thinking as the core logic, aiming to strengthen students' understanding and thinking ability of database design; based on the teaching practice, it was found that students' learning experience and learning concentration were optimized and strengthened [18].…”
Section: Introductionmentioning
confidence: 99%
“…Yao, B. demonstrated the importance of the teaching skills resource base for the teacher's teaching ability training and put forward to speed up the teaching skills development resource base of the informatization construction and optimization and continue to promote the progress of teachers' teaching level [16]. Combefis S et al built a teaching resource database platform for mathematics and computer-assisted learning, which supports students to carry out free searches for rich teaching resources and, to a certain extent, promotes the enhancement of students' independent learning ability and the progress of their learning performance [17]. Lan, Y. researched and built a Lan, Y. researched and constructed knowledge system of database design course with computational thinking as the core logic, aiming to strengthen students' understanding and thinking ability of database design; based on the teaching practice, it was found that students' learning experience and learning concentration were optimized and strengthened [18].…”
Section: Introductionmentioning
confidence: 99%